Identification of formations of soil and subsoil using finite elements modeling - Ouadif Latifa (MATEC Web of Conferences, 2014)
The Soil and subsoil survey are performed by direct and indirect methods. The direct methods are the investigations of field and laboratory while indirect methods are the geophysical methods. These allow, from one or more physical properties, to find out the underground's structure nondestructively. Geophysical methods for characterizing subsurface have long been used, in geotechnical, hydrogeological and environmental studies. For our study, we used the electrical resistivity's method. 52 geoelectric soundings VES was performed with a mesh of 500 m and electrodes distance between 1000 m and 3000 m. The interpretation of these VES allows the determination of the vertical succession of formations in place. In order to have a lateral facies variation, we used geostatistical methods for having adequate data that can be used in the input file of inversion's code Res2Dinv. The 2D images of the subsoil obtained confirm and complement the results of the correlations of oil drilling that are in this region. Thus, the study area also has a horst and graben structure. This study also allowed us to locate the sandstone formations that extend in two places along a North-South direction.